Efecto de recubrimiento de almidón de banano acetilado y aceite esencial de romero en parámetros de conservación de tomate cherry. - Vergara Espinoza, Kevin Alexander; Mejia Verduga, Melina Naryely (Machala : Universidad Técnica de Machala, 2024)
The aim of this study was to develop a coating using acetylated starch from Cavendish banana and rosemary essential oil (Salvia rosmarinus) to investigate its impact on the preservation parameters of cherry tomato (Solanum lycopersicum). The wet method was applied to extract starch with a yield of 31,12 ± 0,48 %, followed by chemical modification by acetylation. Then, the changes of their physical properties such as Swelling Power, Water Absorption Rate, Water Solubility Rate, Oil Absorption Capacity, and syneresis at different temperatures and bulk density were studied, and the chemical composition of the starches modified by acetylation were also evaluated (% Carbohydrates, % Protein, % Fats, % Fat, % Fatty Acids), Protein, Fat, Moisture, Ash, and Fiber. The starch with a high degree of substitution was selected in order to obtain different coating forming solutions based on an experimental design 22, from which cherry tomatoes were coated and placed at (2 - 4°C) and 40% relative humidity for 8 days. It was evidenced that in the modification of starch that by increasing the volume of modifying agent (acetic anhydride), significant changes were identified (0.0025 GS), (p≤0,05). Likewise, changes in their functional properties emerged; such as increase in Swelling power, Water Solubility Index, Water Absorption Index, Oil Retention Capacity as a function of temperature increase (50, 60, 70, 80 and 90°C), while syneresis decreases when stored for 21 days at refrigeration temperatures (0 ± 2 °C). Regarding the chemical composition of the modified starches, there were changes in % Carbohydrate, % Protein, % Moisture and % Ash (p≤0,05), while % Fat and % Fiber (p≥0,05), there were no significant changes. Bulk density was analyzed, showing a tendency to decrease (p≤0,05). On the other hand, it was evidenced that, in the different coating forming solutions, in all the cases of study the % AE Rosemary and the interaction with it % SORBITOL cause significant effects in the variables studied the treatment (p≤0,05). It is observed that both components cause a decrease in TSS, %PP, %IM, and pH, but the opposite situation in Ac. T; the fit models are (TSS = 3.88 + 0.323333*%SORBITOL + 2.03333*%AE - 0.833333*SORBITOL*AE) with R2: 98.0488 and adjusted R2 96.4228; %PP = 2.78667 + 0.77*%SORBITOL + 3.26667*AE - 1.9*SORBITOL*AE) (R2 96.4082 and adjusted R2 93.415); (%Ac. T=0.589167-0.114167*SORBITOL-0.591667*AE+ 0.308333*SORBITOL*AE) (R2 98.7859 and adjusted R2 97.7741); (pH = 3.90583 + 0.259167*SORBITOL + 1.45833*%AE - 0.641667*SORBITOL*AE) (R2 97.5688 and adjusted R2 95.5429) and (%IM = 4.32417 + 4.2975*%SORBITOL + 20.3917*%AE - 10.8083*SORBITOL*AE) (R2 98.5381 and adjusted R2 97.3198); the optimal values that allow minimizing the variables of TSS, %PP, %IM, pH and Ac. T are recorded between values of 0.5% AE w/v and 5% SORBITOL w/v.
En este estudio se desarrolló un recubrimiento utilizando almidón acetilado de banano variedad Cavendish y aceite esencial de romero (Salvia rosmarinus) para investigar su impacto en los parámetros de conservación del tomate Cherry (Solanum lycopersicum). Se aplicó el método húmedo para extraer el almidón con un rendimiento de 31,12 ± 0,48%, seguido de una modificación química por acetilación. Luego se estudiaron los cambios de sus propiedades físicas como Poder de Hinchamiento, Índice de Absorción de Agua, Índice de Solubilidad de agua, Capacidad de Absorción de aceite y sinéresis a diferentes temperaturas y densidad aparente, también se evaluaron asimismo la composición químicas de los almidones modificados por acetilación (%Hidratos de Carbono, % Proteína, % Grasas, % Humedad, % Cenizas y % Fibra), se seleccionó el almidón de alto grado de sustitución con la finalidad de obtener diferentes soluciones formadoras de recubrimientos en base a un diseño experimental 22, de la cual se recubrieron los tomates cherry que se colocaron a (2 - 4 °C) y 40 % humedad relativa durante 8 días; se evidenció que en la modificación del almidón que al incrementar el volumen de agente modificante (anhidrido acético), se identificaron cambios significativos (0,0025 GS), (p ≤ 0,05). Asimismo, surgieron cambios en sus propiedades funcionales; como el aumento del poder de Hinchamiento, Índice de Solubilidad de agua, Índice de Absorción de agua, Capacidad de retención de Aceite en función al incremento de temperatura (50, 60, 70, 80 y 90 °C), mientras que la sinéresis disminuye al estar almacenada durante 21 días a temperaturas de refrigeración (0 ± 2 °C). Con respecto a la composición química de los almidones modificados, hubo cambios en % Carbohidratos, % Proteínas, % Humedad y % Cenizas (p ≤ 0,05), mientras que % Grasa y % Fibra (p ≥ 0,05), no hubo cambios significativos. Se analizó la densidad aparente evidenciándose una tendencia a la disminución (p ≤ 0,05). Por otro lado, se evidenció que, en las diferentes soluciones formadoras de recubrimiento, en todos los casos de estudio el % AE de Romero y la interacción con él % SORBITOL causan efectos significativos en las variables estudiadas el tratamiento (p≤0,05). Observándose que ambos componentes provocan una disminución en SST, %PP, %IM y pH, pero situación contraria en la Ac. T; los modelos de ajuste son (SST = 3,88 + 0,323333*%SORBITOL + 2,03333*%AE - 0,833333*SORBITOL*AE) con R2: 98,0488 y R2 ajustado 96,4228; %PP = 2,78667 + 0,77*%SORBITOL + 3,26667*AE - 1,9*SORBITOL*AE) (R2 96,4082 y R2 ajustado 93,415); (%Ac.T=0,589167-0,114167*SORBITOL-0,591667*AE+ 0,308333*SORBITOL*AE) (R2 98,7859 y R2 ajustado 97,7741); (pH = 3,90583 + 0,259167*SORBITOL + 1,45833*%AE - 0,641667*SORBITOL*AE)(R2 97,5688 y R2 ajustado 95,5429) y (%IM = 4,32417 + 4,2975*%SORBITOL + 20,3917*%AE - 10,8083*SORBITOL*AE) (R2 98,5381 y R2 ajustado 97,3198); los valores óoptimos que permiten minimizar las variables de SST,%PP,%IM, pH Y Ac. T se registran entre valores de 0,5% AE p/v y 5% SORBITOL p/v.
Keywords: RECUBRIMIENTO; ALMIDON; ACETILACION; TOMATE